Regulating the Medical Profession: Challenges and Possibilities of the National Medical Commission Bill, 2017. (June 2018) - Priya, Ritu; Ghodajkar, Prachinkumar
The National Medical Council Bill, 2017, was tabled in Parliament on 29 December 2017 with the proposal to replace the Medical Council of India (MCI) as the regulatory body for medical education and practice in the country. This was the response of the PMO-NITI Aayog Committee, which was formed after the Parliamentary Standing Committee for Health and Family Welfare in its 92nd report strongly indicted the functioning of the MCI and recommended a complete restructuring. The Bill sets out various proposals with the aim to regulate the quality of doctors produced as well as the ethics of their practice. Its content has raised much contestation from the medical fraternity. A host of issues have emerged, such as, what professionalism should mean and what forms of regulation should be put in place, and what mechanisms have to be considered in order to balance the interests of the public and the medical fraternity so that the restructuring that is sorely required can go through.